Measuring the Innovation Potential of Organizations in Andean Countries and the Applicability of the Capabilities, Results, and Impacts of Innovation Model: A Comparative Approach - Verónica Morales; Andrés Robalino-López (Economies)
This study addresses the gap in adequate innovation-measuring frameworks within the Andean Community of Nations (CAN) by analyzing the applicability of the CRI (Capabilities, Results, and Impacts of Innovation) model for assessing the organizational innovation potential in this region. A comparative review of the contemporary innovation measurement methodologies that have been used in Colombia, Peru, and Bolivia reveals that numerous frameworks have assessed innovation skills, yet they have inadequately analyzed innovation outcomes and consequences. In response, this research study contributes a more comprehensive approach—the CRI model—for assessing innovation potential in the Andean context, providing significant insights for policymakers and practitioners aiming to enhance innovation performance.